Social media for the regional anesthesiologist: can we use it in place of medical journals?. Issue 3 (11th November 2019) - Tran, Bryant Winston; Dhillon, Sabrina Kaur; Overholt, Astrid Regina; Huntoon, Marc
Abstract : The regional anesthesia community regularly uses social media for advocacy and education. Well-known leaders in the field are willing to share their opinions with colleagues in a public forum. Some visionaries predict that the influence of social media will soon transcend that of the traditional academic journal. While physicians support the use of social media, an trend may exist toward anecdotal information. Does a lack of online regulation along with a bias towards self-promotion cloud meaningful discussion? In order to avoid the pitfalls of social media, thoughtful communication will help regional anesthesiologists promote their subspecialty. Mindful dialog, promotion of academic journals, and professional etiquette will help maintain a collegial environment.